The Assisi Think Tank Meeting Survey of post-mastectomy radiation therapy in ductal carcinoma in situ: Suggestions for routine practice. (June 2019) - Montero-Luis, A.; Aristei, C.; Meattini, I.; Arenas, M.; Boersma, L.; Bourgier, C.; Coles, C.; Cutuli, B.; Falcinelli, L.; Kaidar-Person, O.; Leonardi, M.C.; Offersen, B.; et al.
Abstract: Background: Risk factors for local recurrence after mastectomy in ductal carcinoma in situ (DCIS) emerged as a grey area during the second "Assisi Think Tank Meeting" (ATTM) on Breast Cancer. Aim: To review practice patterns of post-mastectomy radiation therapy (PMRT) in DCIS, identify risk factors for recurrence and select suitable candidates for PMRT. Methods: A questionnaire concerning DCIS management, focusing on PMRT, was distributed online via SurveyMonkey. Results: 142 responses were received from 15 countries. The majority worked in academic institutions, had 5–20 years work-experience and irradiated <5 DCIS patients/year. PMRT was more given if: surgical margins <1 mm, high-grade, multicentricity, young age, tumour size >5 cm, skin- or nipple- sparing mastectomy. Moderate hypofractionation was the most common schedule, except after immediate breast reconstruction (57% conventional fractionation). Conclusions: The present survey highlighted risk factors for PMRT administration, which should be further evaluated.